Protection and inheritance of folk music from the perspective of intangible cultural heritage: Taking "Mongolian long tune" as an example - Wang, Jianke (International Theory and Practice in Humanities and Social Sciences, 2025)
As an important representative of Mongolian folk music, Mongolian long song is known as the "soul of the grassland". It shows the unique cultural connotation and lifestyle of the Mongolian people with its long melody, free rhythm and rich emotional expression. In 2005, Mongolian long song was listed in the Representative List of the Intangible Cultural Heritage of Humanity by UNESCO. However, the impact of modernization, urbanization and popular culture has made it face many challenges such as the reduction of the inheriting population, the change of cultural environment and the lack of economic support. From the perspective of intangible cultural heritage protection, this paper explores the cultural value and main dilemma of Mongolian long song, and analyzes the protection and inheritance path of long song in combination with policy support, education promotion, digital preservation, cultural activities and innovative communication. The article points out that future protection work should promote the diversified development and international communication of long song on the basis of respecting tradition, and use modern technology and communication means to achieve the sustainable inheritance and innovative development of this intangible cultural heritage.